Facies and architectural variability of sub‐seismic slope‐channel fills in prograding clinoforms, Mid‐Jurassic Neuquén Basin, Argentina. (14th October 2019) - Gan, Yuqian (Philomena); Steel, Ronald J.; Olariu, Cornel; De Almeida, Flávio
Abstract: Most slope‐channel outcrop studies have been conducted at continental margin‐scale on seismic data. However, in foreland and back‐arc deepwater settings, sub‐seismic scale slope channels hold equally important information on deepwater sediment delivery, often in hydrocarbon‐bearing provinces. One such slope‐channel system is examined in Lower Jurassic prograding shelf‐margin clinoforms in Bey Malec Estancia, La Jardinera area, southern Neuquén Basin, Argentina. In a 4 km wide, 300 m tall, slightly oblique‐ to depositional‐dip section of Jurassic Los Molles Formation deepwater slope deposits, seven clinoform timelines were identified by isolated slope‐channel fills with thicknesses less than 50 m. Sedimentary logs, satellite images, a digital elevation model and drone photogrammetry were used to map variations in downslope channel geometry and infill facies. The slope channels are filled with sediment density flow deposits: poorly sorted conglomeratic debrites, structureless sandy high‐density turbidites and well‐sorted, fine‐grained, graded low‐density turbidites. The debrite portion decreases downslope, whereas high‐ and low‐density turbidites increase. A grain‐size analysis reveals a broad downslope fining trend of turbidite and debrite beds within slope channels with increasing water depth, and some notable bypass of conglomeratic facies to the lowermost slope channels and basin floor fans. The architecture of the slope channels changes from lateral to aggradational infill downstream. The Bey Malec clinoforms and its slope channels add new knowledge on downslope changes for sediment delivery in relatively shallow (<500 m water depth), prograding‐dominant deepwater basins. They also highlight one of very few outcropping examples of oblique‐type clinoforms. Abstract : Slope channels are found in an exposed prograding shelf‐margin clinoform outcrop in Bey Malec Estancia, southern Neuquén Basin, Argentina. Several clinoform timelines are mapped on a 4 km wide, 300m tall, slightly dip‐oblique section of Jurassic Los Molles Formation. Seven depositional environments are identified. Sedimentary logs, satellite images, a digital elevation model, and drone photogrammetry were used to track variations in downslope channel geometry and infill facies. The slope channels are all less than 50m in thickness and are filled with sediment density flow deposits. The debrite portion decreases downslope while high and low density turbidites increase. A grain‐size analysis reveals a broad downslope fining trend of turbidite and debrite beds within slope channels with increasing water depth, and some notable bypass of conglomeratic facies to the lowermost slope channels and basin‐floor fans. The architecture of the slope channels changes from lateral to aggradational infill downstream as the aspect ratio of the slope channels increase.